(untitled) (Research, Society and Development, 2022)
Rural education and intercultural knowledge are inseparable elements for a transformative education, under this premise, discussions emerge about the necessary changes in pedagogical practices for basic rural education. Therefore, we have as a starting point the following question: How has this interculturality been carried out in teaching practices? as specific objectives, it is proposed to identify what has been academically discussed in CAPES journals about pedagogical practices for basic education; as well as Analyzing how initial training from an intercultural perspective reflects on pedagogical practices and thus confronting the official guiding bases and their theoretical-practical paths. The methodology used is of a qualitative nature; bibliographic with content analysis through a systematic literature review (RSL) in CAPES journals about pedagogical practices developed for rural education in basic education; followed by the application of a semi-structured questionnaire to teachers in the field of basic education. The results show that research aimed at active practices in elementary school still requires further investigations and intercultural proposals demonstrate better results in terms of engagement, sense of belonging and resignification of school knowledge.